The Consumer Preferences for Apple and Samsung Flagship Smartphones in Surabaya Using Choice-Based Conjoint Analysis - Nisa Desiana; Reny Nadlifatin (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study examines consumer preferences for Apple and Samsung flagship smartphones in Surabaya by applying choice-based conjoint analysis in a realistic multi-attribute choice setting. The research focuses on six attributes that are highly relevant in the premium smartphone market based on expert judgement justification. The study identifies the most preferred product configuration based on estimated utility value, the relative importance of each attribute, and market preference simulation using Lighthouse Studio by Sawtooth Software. The findings indicate that respondents tend to prefer an Apple brand smartphone offered at a lower price range, with larger internal memory, a higher-resolution main camera, a larger battery, and cashback promotion. The results also show that brand and price are the dominant determinants of preference. In addition, the market simulation suggests that a more balanced product concept can outperform the newer or premium alternatives when consumers evaluate trade-offs simultaneously.